Anti-HCV, HBsAg Positive Incidences Among Patients Aged 40 Years and Over Diagnosed with B- Non-Hodgkin’s Lymphoma: A Comparison with General Population of Same Age - Budeebazar, Myagmarjav; Boldbaatar, Delgerbat; Enkhbat, Anir; Sukhbaatar, Myadagsuren; Batsukh, Khishigjargal; Mordorj, Altankhuu; Dungubat, Erdenetsogt; Yagaanbuyant, Dagvadorj; Dashdorj, Naranjargal; Duger, Davaadorj (Central Asian Journal of Medical Sciences, 2019)
Objectives: There are several risk factors contribute to the development of the B-cell Non-Hodgkin’s lymphoma (B-NHL) among which hepatitis B, hepatitis C virus (HBV, HCV) infection, as well as old age, are known to have a signi cant effect. Previous studies examining the relationship between HBV, HCV infection and B-NHL show inconsistent results in different endemic areas. Methods: We compared the hepatitis B surface antigen (HBsAg) and antibody against the HCV (anti-HCV) positive incidences among aged 40 years or older patients who have been newly diagnosed with B-NHL, between 2015 and 2018, to prevalence of hepatitis B and C virus infection in the general population of Mongolia in the same age by data of the general population in hepatitis screening and the results of previous studies on the Mongolian population. Results: A total of 187 patients, newly diagnosed with B-NHL ≥40years of age took part in our study. In case of these two groups, the prevalence of HBsAg in the B-NHL population was close to the general population while anti-HCV positive was signi cantly higher in the B-NHL group (p<.00001). Conclusion: Further studies are needed to clarify the reasons and contributing factors which result situations where the HBV prevalence among B-NHL patients and the general population are not signi cantly different.